2018
DOI: 10.21307/sjcapp-2018-012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy of narrative family therapy for children and adolescents with diverse psychiatric symptomatology

Abstract: Background: Little research has been undertaken on children and adolescents with psychiatric co-morbidity and this group is seldom subject to evidence-based treatment. Equally, there has been little research on creating an evidence base for Narrative Therapy, which means that narrative family therapy (NFT) is seldom available to children and adolescents with a psychiatric disorder. Objective: A single group clinical design was used to examine the efficacy of NFT for children and adolescents with different diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A narrative therapy approach addresses the story line and definition a mother is creating for herself while managing PMAD symptoms and the inevitable postpartum changes. Narrative therapy and the externalization technique can be used in different treatment modalities and to treat a variety of symptoms (Etchison & Kleist, 2000; Jørring & Jensen, 2018). Effective Narrative treatments could include systemic considerations where family and couples can benefit from therapeutic interventions focused on understanding the depression or anxiety symptoms and the importance of safe support systems for the mother and/or father (Cluxton-Keller & Bruce, 2018).…”
Section: Case Study: Narrative Therapy and Pmadsmentioning
confidence: 99%
“…A narrative therapy approach addresses the story line and definition a mother is creating for herself while managing PMAD symptoms and the inevitable postpartum changes. Narrative therapy and the externalization technique can be used in different treatment modalities and to treat a variety of symptoms (Etchison & Kleist, 2000; Jørring & Jensen, 2018). Effective Narrative treatments could include systemic considerations where family and couples can benefit from therapeutic interventions focused on understanding the depression or anxiety symptoms and the importance of safe support systems for the mother and/or father (Cluxton-Keller & Bruce, 2018).…”
Section: Case Study: Narrative Therapy and Pmadsmentioning
confidence: 99%
“…Other studies have emphasised NT as a preventive intervention for children of parents with affective disorders (Focht & Beardslee, 1996) and NT is evidently helpful in the treatment of moderate depression (Jørring & Jensen, 2018; Lopes et al, 2014), the reduction of attention‐deficit/hyperactivity symptoms (Looyeh et al, 2012), psychological distress in children with autism (Cashin et al, 2013), social phobia (Looyeh et al, 2014), and to support the development of social and emotional skills in children. A study by Jørring and Jensen (2018) found that narrative family therapy has a positive effect on young teenagers' own evaluation of the burden of symptoms, and on parents' perceived personal agency regarding the teenager's distress. They point to NT as giving families a language for, and ways of placing themselves in, a more powerful position regarding experienced challenges.…”
Section: Introductionmentioning
confidence: 99%